The effectiveness and safety of micropulse transscleral cyclodiode photocoagulation therapy in glaucoma patients at Groote Schuur Hospital, Cape Town, South Africa - Manyeruke, Stephen (Division of General Surgery, 2023)
Aim To determine the efficacy and safety of micropulse transscleral cyclodiode photocoagulation laser (MP-TSCPC), in terms of intraocular pressure (IOP) reduction, in refractory glaucoma eyes and in blind glaucomatous eyes that were not on antiglaucoma medications. Method 28 consecutive patients were prospectively recruited. Iridex G6 micropulse laser with its P3 probe was used. Baseline variables, including IOP, number of glaucoma medications and visual acuity (VA)were assessed. Success was set at a minimum of 20% reduction in baseline IOP, or a pressure drop to below 21mmHg at 6 months. Results Twenty-eight eyes of 15 female and 13 male glaucoma patients were enrolled. The mean baseline IOP was 40±11mmHg and the mean post laser pressures were 23±10mmHg at 1 week, 25±11mmHg at 4 weeks, 32±12mmHg at 12 weeks and 27±13mmHg at 24 months, representing a percentage drop of 40%, 35%, 30% and 35%, respectively. There was a reduction of one anti glaucoma agent in 11 (39%) patients. The overall success rate of MP-TSCPC was 71% with no serious complications noted. Conclusion In this small cohort of patients, micropulse transscleral laser cyclophotocoagulation was safe and effective in reducing IOP in glaucoma patients, with a success rate of 71%. Further studies are required to verify this finding.